Torsion and the electromagnetic field - De Andrade, V. C. [UNESP]; Pereira, J. G. [UNESP] (World Scientific Publishing, 1999)
In the framework of the teleparallel equivalent of general relativity, we study the dynamics of a gravitationally coupled electromagnetic field. It is shown that the electromagnetic field is able not only to couple to torsion, but also, through its energy-momentum tensor, produce torsion. Furthermore, it is shown that the coupling of the electromagnetic field with torsion preserves the local gauge invariance of Maxwell's theory.